Teacher Growing Pains - Carolina Mancuso (Journal of the Assembly for Expanded Perspectives on Learning, 2001)
Reflecting on a teacher education course which incorporated experiential learning in an exploratory pedagogy, the author examines how the relationship between teachers and students can affect both personal and professional lives, particularly in periods of individual transition.